IDENTIFIKASI ALUR SUNGAI PURBA DAN ENDAPAN PLASER DI PERAIRAN LEMBAR PETA 1612 KALIMANTAN SELATAN - Arifin, Lukman (Jurnal Geologi dan Sumberdaya Mineral, 2011)
Placer deposits is suggested to be within the paleo channels present in the study area. It can be identified from high resolution single channel seismic profiles. These paleo channels occurred within sequence D and marked by the presence of cut and fill characters on the seismic record. The placer were deposited during the activity of paleo channel in the regression period. Placer deposits are probably derived from igneous and metamorphic rocks of Mesozoic age found around the Meratus Mountain as the source of Recent placer deposits. The sediments composed of quartz and clay minerals such as kaolinite and montmorilonite.Keywords: placer, paleo channel, quartz, clay mineral, South Kalimantan